Microwave Radiometer for Detecting Internal Temperature of Biological Tissue - Qin, Ruiqi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Microwave radiometers are gaining increasing attention for their ability to measure the temperature inside biological tissues, a capability that is of great significance in medical applications such as cancer treatment and burn therapy. However, there is still a research gap in their precise application in these areas. This study aims to explore the feasibility of using microwave radiometers to detect subcutaneous tissue temperature by analyzing low-frequency microwave signals. A miniature radiometric sensor was systematically experimented with in the study to evaluate its sensitivity, stability, and accuracy in real-time temperature monitoring. The results showed that the radiometer was able to accurately track subcutaneous temperature changes within a small error range, confirming its applicability in non-invasive medical applications. In particular, this study highlighted the effectiveness of the radiometer in microwave ablation therapy and biomedical thermoacoustic imaging, demonstrating its potential to improve diagnostic accuracy and therapeutic efficacy. Microwave radiometers have shown significant results in cancer treatment through microwave ablation therapy, image-guided precision therapy, and minimally invasive treatment. In addition, its application in biomedical microwave thermoacoustic imaging shows great potential to provide high-resolution and high-contrast images for cancer diagnosis and brain imaging. The research of microwave radiometers in the biomedical field has important practical significance and broad development prospects, which will have a positive impact on human health and medical care.